Pelatihan Pengembangan Motif dan Warna Bagi Penenun Songket Lombok di UD. Undur Pasang Sukarara - Sri Sukarni; Pyo Apriliana Munawaroh; L. Aswandi Mahroni G; Mi’rajus Subyan Rahmat (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This community service aimed to train weavers in order to have ability and skill in developing motif and color on Lombok songket. The community service is done in UD. Undur Pasang that produces and sells Lombok songket and the weavers as the participants of this community service. Preparation, implementation, monitoring and evaluation are the three methods applied in this community service. In preparation phase, through discussion between team and weavers. In the second phase, community service team prepare materials for training and trained those weavers to develop motifs by drawing and adjust the image on color of songket and followed by application in weaving activity. In monitoring and evaluation phase, community service team observed all results related to new motifs and color of songket. Through this training activity, weavers do not only have ability to draw and determine the point or line that become benchmark of formation motifs but also skill in harmonizing the motifs with yarn during weaving. The result of this training produced new motifs and color of songket without changing the characteristic motif ofÂ UD. Undur Pasang products.